Pronecrotic mixed lineage kinase domain‐like protein expression is a prognostic biomarker in patients with early‐stage resected pancreatic adenocarcinoma. Issue 17 (29th May 2013) - Colbert, Lauren E.; Fisher, Sarah B.; Hardy, Claire W.; Hall, William A.; Saka, Burcu; Shelton, Joseph W.; Petrova, Aleksandra V.; Warren, Matthew D.; Pantazides, Brooke G.; Gandhi, Khanjan; Kowalski, Jeanne; Kooby, David A.; et al.
Abstract : BACKGROUND: Mixed lineage kinase domain‐like protein (MLKL) is a necrosome component mediating programmed necrosis that may be an important determinant of cancer cell death. The goal of the current study was to evaluate the prognostic value of MLKL expression in patients with pancreatic adenocarcinoma (PAC). METHODS: Tissue from 80 patients was collected from a prospectively maintained database of patients with PAC who underwent pancreaticoduodenectomy between January 2000 and October 2008. Immunohistochemistry analysis was performed and scored using an established scoring system. Kaplan‐Meier survival curves were generated for recurrence‐free survival (RFS) and overall survival (OS) for all patients and for patients receiving adjuvant chemotherapy. MLKL scores were correlated with RFS and OS using univariate and multivariate Cox regression analyses incorporating clinically relevant covariates. RESULTS: The median age of the patients was 63 years and 53% were men. Low MLKL expression was associated with decreased OS (6 months vs 17 months; P = .006). In the subset of 59 patients who received adjuvant chemotherapy, low MLKL expression was associated with decreased RFS (5 months vs 15 months; P = .006) and decreased OS (6 months vs 19 months; P < .0001). On multivariate analysis, low MLKL expression was associated with poor OS in all patients (hazards ratio, 4.6 [95% confidence interval, 1.6‐13.8]; P = .006) and in patients receiving adjuvant chemotherapy (hazards ratio, 8.1 [95% confidence interval, 2.2‐29.2]; P = .002). CONCLUSIONS: Low expression of MLKL is associated with decreased OS in patients with resected PAC and decreased RFS and OS in the subset of patients with resected PAC who receive adjuvant chemotherapy. The use of this biomarker in patients with PAC may provide important prognostic information. Cancer 2013;119:3148–3155 . © 2013 American Cancer Society . Abstract : Low expression of mixed lineage kinase domain‐like protein (MLKL) in patients with resected pancreatic adenocarcinoma is associated with decreased overall survival in those who undergo surgical resection and with decreased recurrence‐free and overall survival in the subset of patients receiving adjuvant chemotherapy. MLKL warrants further exploration as a potential prognostic biomarker in patients with resected pancreatic adenocarcinoma.